Miejsce metafor w badaniach nad komunikacją - Domaradzki, Mikołaj (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2012)
The purpose of the present paper is to discuss several metaphorical conceptualizations of the phenomenon of communication from the perspective of cognitive linguistics. Apart from the purely linguistic and philosophical issues, the article touches upon the questions that concern the process of teaching and learning a foreign language (especially the so called "radically different one"). The thesis about our essentially metaphorical understanding of the phenomenon of communication, widely acknowledged in cognitive linguistics, is supported by empirical data drawn from Arabic and several Indo-European languages. Subsequently, the thesis is taken as a point of departure for discussing such issues as the problem of cross-linguistic variation of metaphors and their biological motivation. The paper consists of three sections: the first one examines the metaphor of communication as transfer, the second considers the metaphor of communication as enlightening, whereas the third presents some philosophical observations. The most important conclusion that is drawn here has it that the potential universality of various metaphorical conceptualizations is a very useful heuristic and didactic tool, for the existence of a common ground between languages that are genetically unrelated makes it possible not only to account for the ease with which certain elements of the target language can be translated into the source language, but also to hypothesize about the general mechanisms that are responsible for understanding and acquiring the (radically) different target language. Needless to say, such hypotheses are of paramount importance for the process of teaching and learning a foreign (especially radically different) language.